2016
DOI: 10.15171/bi.2016.29
|View full text |Cite
|
Sign up to set email alerts
|

Lactobacillus species mediated synthesis of silver nanoparticles and their antibacterial activity against opportunistic pathogens in vitro

Abstract: Introduction: Application of lactic acid bacteria for synthesis of silver (AG) nanoparticles (NPs) could be a good ecological friendly alternative to chemical and physical methods. The objective of this study was to investigate the biosynthesis of silver NPs using Lactobacillus strains and to compare their monosaccharide composition of capsular exopolysaccharides and the antibacterial activity of synthesized nanoparticles. Methods: The washed cells of 22 Lactobacillus strains were used for in vitro silver n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
23
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(26 citation statements)
references
References 12 publications
3
23
0
Order By: Relevance
“…The monosaccharide composition of capsular heteropolysaccharides from different Lactobacillus strains could explain the ability to reduce the silver ions and produce AgNPs with different sizes and size distribution. The differences in antibacterial activity of AgNPs assayed, as in our experiment, by agar well diffusion method were explained by authors as influenced by the capsular biopolymer composition (45). Also, a recent study (46) presented the biosynthesis of AgNPs for biomedical applications, mediated by extracellular pigment produced by Thalaromyces purpurogenus, with particles size from 4 to 41 nm diameter, polydispersed and stable, exhibiting a surface plasmon resonance at around 410 nm but a more variable shape of nanoparticles (spherical, hexagonal, rodshaped or triangular) than in the present research.…”
Section: Discussionmentioning
confidence: 50%
“…The monosaccharide composition of capsular heteropolysaccharides from different Lactobacillus strains could explain the ability to reduce the silver ions and produce AgNPs with different sizes and size distribution. The differences in antibacterial activity of AgNPs assayed, as in our experiment, by agar well diffusion method were explained by authors as influenced by the capsular biopolymer composition (45). Also, a recent study (46) presented the biosynthesis of AgNPs for biomedical applications, mediated by extracellular pigment produced by Thalaromyces purpurogenus, with particles size from 4 to 41 nm diameter, polydispersed and stable, exhibiting a surface plasmon resonance at around 410 nm but a more variable shape of nanoparticles (spherical, hexagonal, rodshaped or triangular) than in the present research.…”
Section: Discussionmentioning
confidence: 50%
“…This biosynthesis involved the formation and stabilisation of ZnO NPs. In addition, the EPS secreted by L. plantarum was reported in Garmasheva et al 's [15] study, where the reduction and biosorption of metal ion were involved, leading to the formation of NPs. However, this formation was contradicted with this study's finding as the TA4 strain investigated in this study did not produce EPS.…”
Section: O-h Stretching and N-h Asymmetric Stretchingmentioning
confidence: 91%
“…Furthermore, LAB efficacy in mediating the synthesis of ZnO NPs was observed in several studies [6,[9][10][11][12]. It was reported that LAB can produce selenium [13], gold [14], and silver NPs [15]. Overall, LAB is a useful cell factory for the formation of NPs due to these features.…”
mentioning
confidence: 98%
“…Moreover, using bacteria for the biosynthesis of ZnO NPs has significant advantages due to the production of functional biomolecules in the supernatant, which can reduce the metal ions into metal NPs 12,19 . In addition, the cell biomass of bacteria could act as a nanofactory in ZnO NPs' production due to the presence of a functional group on the bacterial cell that reduces the metal ions into metal NPs 20,21 .…”
mentioning
confidence: 99%